Governance Structures, Cultural Distance, and Socialization Dynamics: Further Challenges for the Modern Corporation - Georg Schwesinger; Stephan Müller; Sarianna M. Lundan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper relates cultural distance and governance structures. We suggest a model of cultural evolution that captures the idiosyncratic socialization dynamics taking place in groups of communicating and interacting agents. Based on these processes, cultural distance within and between groups or organizational units develops. Transaction cost theorists associate higher cultural distance with higher transaction costs. Therefore, one problem of economic organization is assessing alternative governance structures in terms of the socialization dynamics they enable that entail different intraorganizational transaction costs. We assume that transaction can be organized within governance structures that allow transaction cost economizing socialization processes.
Keywords: D21; D23; C61; 330